Areas, Circles and Squares!

Geometry Level 3

A square is inscribed in the two intersecting unit circles with centers O O and O O' as shown above.

If the area A d A_{d} of the red region can be expressed as A d = a ( π b ) + b ( c b ) d A_{d} = \dfrac{a(\pi - b) + b(\sqrt{c} - \sqrt{b})}{d} , where a , b , c a,b,c and d d are coprime positive integers, find a + b + c + d a + b + c + d .


The answer is 20.

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

1 solution

Rocco Dalto
May 8, 2021

R ( 1 a 2 , a 2 ) R(\dfrac{1 - a}{2}, \dfrac{a}{2}) is on the circle ( x 1 ) 2 + y 2 = 1 2 a 2 + 2 a 3 = 0 (x - 1)^2 + y^2 = 1 \implies 2a^2 + 2a - 3 = 0 \implies

a = 7 1 2 a = \dfrac{\sqrt{7} - 1}{2} dropping the negative root.

\implies the area of the square A s = ( 7 1 2 ) 2 = 4 7 2 A_{s} = (\dfrac{\sqrt{7} - 1}{2})^2 = \dfrac{4 - \sqrt{7}}{2}

Solving x 2 + y 2 = 1 x^2 + y^2 = 1 and x 2 2 x + 1 + y 2 = 1 2 x 1 = 0 x = 1 2 y = ± 3 2 x^2 - 2x + 1 + y^2 = 1 \implies 2x - 1 = 0 \implies x = \dfrac{1}{2} \implies y = \pm\dfrac{\sqrt{3}}{2} \implies

The point of intersection of the two circles is ( 1 2 , ± 3 2 ) (\dfrac{1}{2},\pm\dfrac{\sqrt{3}}{2}) \implies the base, height and m S O T m\angle{SOT} of S O T \triangle{SOT} are

S T = 3 , h e i g h t = 1 2 \overline{ST} = \sqrt{3}, height = \dfrac{1}{2} and m S O T = 2 π 3 A S O T = 3 4 m\angle{SOT} = \dfrac{2\pi}{3} \implies A_{\triangle{SOT}} = \dfrac{\sqrt{3}}{4}

and

A s e c t o r S O T = 1 2 ( 2 π 3 ) = π 3 A_{sector{SOT}} = \dfrac{1}{2}(\dfrac{2\pi}{3}) = \dfrac{\pi}{3} \implies The area of the region between the two circles is

I = 2 ( A s e c t o r S O T A S O T ) = 4 π 3 3 6 I = 2(A_{sector{SOT}} - A_{\triangle{SOT}}) = \dfrac{4\pi - 3\sqrt{3}}{6} \implies the desired area is A d = I A s = A_{d} = I - A_{s} =

4 π 3 3 12 + 3 7 6 = \dfrac{4\pi - 3\sqrt{3} - 12 + 3\sqrt{7}}{6} = 4 ( π 3 ) + 3 ( 7 3 ) 6 = a ( π b ) + b ( c b ) d \dfrac{4(\pi - 3) + 3(\sqrt{7} - \sqrt{3})}{6} = \dfrac{a(\pi - b) + b(\sqrt{c} - \sqrt{b})}{d}

a + b + c + d = 20 \implies a + b + c + d = \boxed{20} .

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...